Application of the Quantum Learning Model Assisted with Audio Visual Media to Improve Tembang Dolanan's Singing Skills of Students at SD Negeri 1 Sukomangu - EUNIKE DWI LESTARI; RHOKHAYATI RHOKHAYATI (Pusat Unggulan Ipteks Javanologi Universitas Sebelas Maret, 2024)
This research aims to improve the singing skills of Tembang Dolanan through the application of the Quantum Learning model assisted by audio-visual media. This type of research is quantitative research using a one-group pretest-posttest design experimental approach. The research was carried out on grade 1 students at SD Negeri 1 Sukomangu, Purwantoro District, Wonogiri Regency, totaling 17 students. Method of collecting data using observation and tests. The data analysis used is a quantitative data analysis technique. The results of the research show that the application of the Quantum Learning model can improve the singing skills of Dolanan songs well. This success was proven by a significant increase in 7 aspects of the assessment criteria which led to an increase in the scores obtained by 17 students in class 1. The scores obtained for the assessment aspects showed an increase, it was proven that in all aspects of the assessment criteria there were students who obtained the maximum score, and were no longer found. students who get a score of 1. The total score obtained also shows that there is an increase of 7 to 21 points from the pre-test score. Success was also proven by an increase in the class average score from the pre-test score of 69.29 to 80.82 in the post-test and an increase in the class average score of 11.53.